The dictionary of nautical literacy - McKenna, Robert (International Marine/McGraw-Hill, 2001)
"The Dictionary of Nautical Literacy is the first book to chart the culture of the sea - an entertaining desk reference for all those with an interest in things nautical. Robert McKenna avoids both the overly trivial and the overly familiar. Consequently, unlike other nautical dictionaries, which tend to concentrate exclusively on defining parts of a ship and sailor slang, The Dictionary highlights significant (and sometimes humorous) ideas, events, and individuals, and explains their relevance in maritime culture. Abbott and Costello Meet Captain Kidd, Admiral Nelson, Davy Jones's locker, the Loch Ness monster, Little Toot, scurvy, sea legs, and zebra mussels - it's all here."--BOOK JACKET.